Optimasi Celah Geometrik Ripple Mill dalam Menyeimbangkan Efisiensi Pemecahan Biji dan Integritas Inti Sawit di PKS Bah Jambi - Maren sius girsang; Jhon Supriadi Purba (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
In the palm oil extraction process, the efficiency of the ripple mill is critical to maximizing kernel recovery while minimizing losses. This study aims to evaluate the impact of the clearance between the rotor bar and the ripple plate on the cracking efficiency and kernel quality at the PKS Bah Jambi palm oil mill. Experimental tests were conducted under normal industrial operating conditions by varying the rotor barâ€“ripple plate distance at four levels: 8 mm, 9 mm, 10 mm, and 11 mm. A 1000-gram sample of the cracked mixture was collected for each setting and manually separated into five fractions: whole nuts, cracked nuts, whole kernels, broken kernels, and shells to calculate the cracking efficiency and mass percentages. The results demonstrate that the geometric clearance significantly controls the quality and efficiency of nut cracking. Increasing the clearance from 8 mm to 11 mm led to a significant decrease in cracking efficiency from 98.05% to 94.57%, falling below the mill’s minimum standard of 97%. While wider clearances offered better protection for the kernels (reducing broken kernels), they resulted in higher kernel losses due to the increased volume of uncracked and partially cracked nuts.To maintain optimal performance, the mill management should standardize the rotor-plate distance at 8â€“9 mm, which ensures an efficiency rate above 97% while maintaining acceptable kernel breakage levels. It is recommended that this setting be integrated into the Standard Operating Procedures (SOP), supported by routine wear inspections and the reactivation of nut grading drums to ensure feedstock uniformity and stable mill performance. Keywords: Ripple Mill, Cracking Efficiency, Palm Oil Mill.